Effect of sulphur, zinc and boron on growth and yield of irrigated Indian mustard (Brassica juncea L) in Bundelkhand region - Narendra Kumar Bhinda,; Yogeshwar Singh,; Anoop Kumar Dixit,; Dhiraj Kumar, (Journal of Oilseed Brassica, 2026)
A field experiment was carried out to assess the effect of different levels of sulphur, zinc and boron on growth and yieldof Indian mustard (Brassica juncea L) during 2019-20. Results revealed that the growth parameters were maximum withthe application of 40 kg S ha-1 at 60 and 90 days after sowing (DAS) and as well as at harvest, which was statistically atpar with 20 kg S ha-1 while significantly higher over 0 kg S ha-1. In case of zinc and boron levels maximum value of growthparameters were recorded with 5.0 kg Zn ha-1 at 60 and 90 DAS. The highest seed yield, stover yield, harvest index, oilcontent and oil yield were recorded with the application of 40 kg S ha-1, which was significantly higher over 0 kg S ha-1.Among zinc and boron levels, the application of 2.5 kg Zn + 0.5 kg B ha-1 produced higher seed yield, stover yield,harvest index, oil content and oil yield. Interactive effect of S, Zn and B on seed yield and oil yield was also foundsignificant. Maximum seed yield was recorded with the application of 40 kg S along with 2.5 kg Zn + 0.5 kg B ha-1 whileoil yield was maximum with application of 40 kg S along with 2.5 kg Zn.